A Beam Design Aid for Structural Tubing - Siddiqui, Faruq M.A. (Engineering Journal, 1986)
Structural tubing is used primarily by designers for pipe and equipment supports. Recently, tubes have also been used in other major structures. Square and rectangular structural tubes have excellent resistance to lateral torsional buckling depending on their lateral dimensions. They are also pleasing aesthetically and assure cleanliness by eliminating dirt-collecting flange areas. The 1978 AISC Specification1 has explicit provisions for the use of square or rectangular tubes for beams. However, there are no beam design aids in the steel manual for tubes, other than section property information. Design aids are available however in the form of "Beam Load Tables" showing allowable uniform loads for laterally supported beams.